Risk Stratification Of Signs Of Possible Serious Bacterial Infection For Prediction Of Mortality Among Young Infants - Singh, Raashi; Mir, Yaseer Ahmad; Chellani, Harish; Kumar, Harshit (Indian Journal of Child Health, 2024)
Objective: Possible serious bacterial infection (PSBI) is one of the leading causes of infant mortality. Based on WHO multi-centric study, signs of PSBI are categorized into: signs of clinical severe infection (CSI) and signs of critical illness (CI). Assessment of signs of PSBI helps to divide infants into risk groups for appropriate management and prognostication. This study aimed to assess risk stratification of signs of PSBI among young infants (0- 59 days of age) by correlating signs of PSBI with mortality. Methods: In this hospital-based prospective cohort study, 220 young infants with signs of PSBI were recruited. Infants were categorized into two: those with signs of CSI and those with signs of CI. Correlation of each sign of PSBI was done with mortality. Time to death was assessed by using the Kaplan Meier survival analysis. Results: 220 infants were analyzed for outcomes. Signs of CSI including fever, fast breathing, poor feeding, and movement only on stimulation had a low fatality rate; however low body temperature and severe chest pain was associated with high mortality of 20% and 9%, respectively. CI signs – convulsion, no movement at all, and no feeding at all were associated with high death rates of 14%, 63.7%, and 47.4% respectively. The majority of deaths were occurred within 48 hours of presentation. Conclusions: Mortality was high in infants with low body temperature, chest pain, or any sign of CI. Risk stratification based on clinical signs could help prioritize infants in need for urgent intervention and thus decrease infant mortality.